APPLICATION OF BIODEGRADABLE POLYMERS IN THE MANUFACTURE OF NONWOVEN FILTER MATERIALS - БУЛГАКОВ, Є. С.; САВЧЕНКО, Б. М.; ІСКАНДАРОВ, Р. Ш.; СВІСТІЛЬНІК, Р. Ф.; ПУШКАРЬОВ, Д. В. (Technologies and Engineering, 2023)
Purpose. The purpose of this article is to investigate the possibility of obtaining nonwoven materials from polylactic acid and to examine their properties. Methodology. Nonwoven polymer materials from polypropylene and polylactic acid was produced on a laboratory setup using the melt-blown method, which involves aerodynamic spraying of the melt onto a receiving drum. The size distribution of the elementary fibers based on their apparent diameter was analyzed through software analysis of images captured by optical microscopy. The images were obtained using a optical microscope with a digital camera attached. ImageJ software with the specialized DiameterJ plugin was used for image analysis. The filtration efficiency of the nonwoven material was evaluated in an air environment using a testing stand equipped with a Temtop PMD331 aerosol particle counter (certified according to ISO-21501). Findings. The possibility of manufacturing nonwoven material from polylactic acid on equipment suitable for polypropylene processing has been experimentally confirmed. The parameters of fiber structure and their filtration efficiency were investigated. The nonwoven material with same square weight from polylactic acid has a 10% lower average fiber diameter compared to the nonwoven material from polypropylene. Nonwoven polymer materials manufactured with the same square weight exhibit similar filtration efficiency values. The nonwoven material from polylactic acid is characterized by improved filtration efficiency and a smaller average fiber diameter. Nonwoven material produced from polylactic acid can be used as potential biodegradable replacement of polypropylene based on material structure and filtration performance. Originality. The parameters of fiber structure in nonwoven materials made from polypropylene and polylactic acid were investigated using image analysis software. The influence of fiber diameter distribution on the filtration efficiency of the materials was studied. Practical value. The feasibility of processing polylactic acid on equipment designed for polypropylene, with the ability to adjust the parameters of the nonwoven material structure within wide ranges, has been established. Equipment designed for polypropylene polymer is well suitable for processing polylactic acid with different temperature settings.